Language maintenance and competing priorities at the Portuguese Settlement, Malacca - Lee, Ei Leen * (Ritsumeikan Center for Asia Pacific Studies, 2011)
Papia Kristang or Malacca Creole Portuguese, is the „language‟ of the descendents of the Portuguese who conquered Malacca in 1511 and it has been spoken by the Kristang speech community at the Portuguese Settlement, Malacca for at least five centuries. However, in 1984 the creole is listed on the UNESCO Red Book of Endangered Languages. A community‟s awareness of and its response to its endangered language situation is a fundamental factor that will determine the future of its language. While the quest for socio-economic development and economic mobility over language preservation are reasons often cited for the lack of focus to reverse the language shift taking place, often there are other issues from a minority community‟s perspective that influence its priorities. Data from interviews and an attitude and subjective vitality (ASV) questionnaire indicate that the belief systems of the community and the socio-political context of inter-group relations in the country are interlinking factors that determine language maintenance and competing priorities at the Portuguese Settlement. In conclusion, the lack of urgency for language maintenance is best analyzed and understood by taking into consideration the context of its minority status and intergroup relations in the country.